A Study of the Perceived Professional Needs of ESL Teacher Educators in Malaysian Teacher Training Colleges - Mohd Ali, Leela (1991)
In Malaysia,the roles and responsibility of ESL teacher educator sin the development of English language teaching and learning are crucial. The Cabinet Committee Report on the Implementation of National Education Policy (1979) stipulates that teacher educators who fall short of desired professional competence and performance be sent back to their original posts. This is indicative of the high level of professional is mexpected of teacher educators. For ESL teacher educators,who are part of the general milieu of teacher educators, this would mean that they have to work towards the upgrading of their professionalism. It is expected that the findings of this study will facilitate efforts at upgrading the professionalism of ESL teacher educators attached to the Malaysian teacher training colleges.